Collective behavior diverges independently of the benthic-limnetic axis in stickleback - Kevin M. Neumann; Lucas Eckert; Damaris Miranda; Andrew Kemp; Alison M. Bell (Behavioral Ecology and Sociobiology, 2025)
Comparing populations across replicate environments or habitat types can help us understand the role of ecology in evolutionary processes. If similar phenotypes are favored in similar environments, parallel evolution may occur. Collective behavior, including collective movement and social networks, can play a key role in the adaptation by animals to different environments. However, studies exploring the parallelism of collective behavior are limited, with research traditionally focusing on morphological traits. Here, we asked if collective behavior varies consistently across replicate populations of benthic and limnetic three-spined stickleback ( Gasterosteus aculeatus ). There were repeatable, population-level differences in collective behavior in a common garden experiment, with some populations forming groups that were more cohesive and with higher strength and clustering coefficients. However, these differences were not predicted by ecotype (benthic vs. limnetic). Latency to emerge and morphology did consistently differ between ecotypes, and there were no correlations between these traits and collective behavior. Together, these results suggest that collective behavior diverges, but not in a way that is associated with variation along the benthic-limnetic axis. By examining multiple traits, we show how phenotypic evolution can be occurring in parallel and non-parallel ways at the same time. This study further highlights that the classification of habitat types may only be relevant for certain traits, with collective behavior potentially changing in a more nuanced manner.